Cathepsin E Deficiency Ameliorates Graft-versus-Host Disease and Modifies Dendritic Cell Motility - Mengwasser, Jörg; Babes, Liane; Cordes, Steffen; Mertlitz, Sarah; Riesner, Katarina; Shi, Yu; McGearey, Aleixandria; Kalupa, Martina; Reinheckel, Thomas; Penack, Olaf (Frontiers in Immunology, 2017)
Microbial products influence immunity after allogeneic hematopoietic stem cell transplantation (allo-SCT). In this context the role of Cathepsin E (Ctse), an aspartate protease known to cleave bacterial peptides for antigen presentation in dendritic cells (DCs), has not been studied. During experimental acute graft-versus-host disease (GVHD), we found infiltration by Ctse positive immune cells leading to higher Ctse RNA- and protein levels in target organs. In Ctse deficient allo-SCT recipients, we found ameliorated GVHD, improved survival and lower numbers of tissue infiltrating DCs. Donor T cell proliferation was not different in Ctse deficient- vs. WT allo-SCT recipients in MHC-matched and MHC-mismatched models. Furthermore, Ctse deficient DCs had an intact ability to induce allogeneic T cell proliferation, suggesting that its role in antigen presentation may not be the main mechanism how Ctse impacts GVHD. We found that Ctse deficiency significantly decreases DC motility in vivo, reduces adhesion to extra cellular matrix (ECM) and diminishes invasion through ECM. We conclude that Ctse has a previously unrecognized role in regulating DC motility that possibly contributes to reduced DC counts and ameliorated inflammation in GVHD target organs of Ctse deficient allo-SCT recipients. However, our data does not provide definite prove that the observed effect of Ctse-/- deficiency is exclusively mediated by DCs. A contribution of Ctse-/- mediated functions in other recipient cell types, e.g. macrophages, cannot be excluded.